Assessment of Microplastic Contamination and its Ecological Impact on the Aquatic Ecosystem of River Sone at Old Shahabad - Singh, Anupama; Singh, Sunil Kumar; Verma, Rajesh (Journal of Discoveries in Applied and Natural Science, 2026)
Microplastic pollution has emerged as a pervasive environmental threat in freshwater ecosystems, yet data from Indian rivers remain limited. This study investigates the ingestion and trophic transfer of microplastics across plankton, benthic macroinvertebrates, and fish in the River Sone, Bihar, India, focusing on midstream (Dehri-on-Sone) and downstream (Koilwar) sites. Biological samples were collected seasonally (pre-monsoon, monsoon, post-monsoon) and analyzed for microplastic abundance, morphology, size, and polymer composition using stereo microscopy, FTIR, and Raman spectroscopy. Microplastics were detected in all trophic levels, with the lowest abundance in plankton (2.1–6.4 particles m⁻³) and the highest in fish (7.2–28.9 particles individual⁻¹), indicating trophic transfer and accumulation. Fibers were the dominant morphology, and polyethylene, polypropylene, and polystyrene were the most common polymers. Seasonal variation revealed elevated microplastic ingestion during pre- and post-monsoon periods, reflecting hydrological influences on particle availability and sediment resuspension. The results highlight the role of benthic macroinvertebrates as intermediate reservoirs, facilitating microplastic transfer to higher trophic levels. Continuous ingestion poses potential sub-lethal physiological stress, ecological disruption, and human health risks, especially considering the consumption of local fish. This study provides the first evidence of trophic amplification of microplastics in the River Sone and underscores the urgent need for continuous monitoring, improved waste management, and policy interventions to mitigate plastic contamination in Indian freshwater ecosystems. The findings contribute to a broader understanding of microplastic dynamics in tropical riverine environments and their implications for freshwater biodiversity and food security.